Study on Role of Radio for Rural Education in Pakistan - Jumani, Nabi Bux (2009)
It was found that the majority of the listeners possessed radio sets and was getting benefit from the educational programmes of radio. The programmes were informative and motivating. The strategies of radio for rural education were appreciable because these infused mobility, widened horizon of rural people and focused attention on the goals and problems of rural people. It could be used to enhance literacy (through distance and non-formal education). The producers/comperes were found keenly interested in their job. It was revealed that priority was given to education and rural development programmes of radio. Programmes needed detail and summary at the end. Furthermore language was not easy. Mobile radio station was needed for rural educational programme to cater to the needs of far flung areas. School broadcast (distance and non-formal teaching) was the need of the day. Social workers/opinion leaders opined that there was need of developing self reliance. Radio provides guidance to rural people in solving the problems of rural development. They felt the need of starting school broadcasting. Radio was being utilized for apprising villagers with their problem. There was need of maintaining more educational programmes. Rural programmes were to be in mother tongue. It was recommended that for educational purposes Radio Pakistan and AIOU may produce programmes which have their strong links/roots in the surroundings of the rural people. Radio schools like Interactive Radio instruction (IRI) may be used for effective teaching learning process in rural areas. Time of educational programmes should be enhanced. Programmes like radio rural forum may be started as well as open broadcasting should be adopted for rural development programme. (Contains 5 tables.)
Keywords: Distance Education; Educational Technology; Foreign Countries; Instructional Effectiveness; Nonformal Education; Radio; Rural Areas; Rural Development; Rural Education; Teaching Methods

Evaluating large‐scale interactive radio programmes - Potter, Charles; Naidoo, Gordon (Distance Education, 2009)
This article focuses on the challenges involved in conducting evaluations of interactive radio programmes in South Africa with large numbers of schools, teachers, and learners. It focuses on the role such large‐scale evaluation has played during the South African radio learning programme’s development stage, as well as during its subsequent sustained implementation phase. The model evolved for evaluation of interactive radio instruction is based within the context of a shoestring/real‐world evaluation tradition, where funding for internal evaluation has been limited over the period of the programme’s development to scale, necessitating focused use of resources in a longitudinal evaluation design. The evaluation approach is participatory and multimethod, linking the requirements of external summative evaluation conducted for accountability, with data yielded by internal (formative and developmental) evaluation. This is done through internal and formative evaluative studies of limited scope, combined with developmental classroom‐based evaluation based on the logic of project team members working with teachers to promote the programme’s self‐evaluative capacity.
Keywords: distance education; interactive radio instruction; large‐scale implementation; modalities; pedagogy; programme evaluation; shoestring/real‐world evaluation

Improving educational quality with interactive radio instruction : a toolkit for policymakers and planners - Anzalone, Stephen; Bosch, Andrea (Africa Region Human Development Working Papers Series No.52, 2005)
This toolkit offers a timely compilation and analysis of recent experience of interactive radio instruction (IRI) in Africa and elsewhere. It explains the IRI concept. It guides the reader through the process of determining when IRI might be appropriate in a given context, and it describes the steps in setting up an IRI program. The authors emphasize the critical factors for success, including appropriate policy frameworks as well as planning for the necessary investment and sustainability. The report is organized as follows: Chapter 1 generally describes the IRI methodology and discusses the effectiveness, scale, and sustainability of the IRI approach. Chapter 2 then outlines steps for assessing the potential and appropriateness of IRI for improving educational quality in primary school classrooms in a given country, and chapter 3 leads the reader through a guided decision-making process for identifying the issues involved in applying the IRI methodology in particular country contexts. Two appendixes give summary data and illustrate, through brief vignettes, how IRI programs have worked in Sub-Saharan African countries. The Resources section contains further useful information, much of it available online.
Keywords: Commitment; ___working_potential_duplicate; broadcasting; cost

Tuned in to Student Success: Assessing the Impact of Interactive Radio Instruction for the Hardest-To-Reach - Ho, Jennifer; Thukral, Hetal (Education Development Center, 2009)
This study reviews student assessment data collected from 15 EDC projects to determine the impact of interactive radio instruction (IRI) on student achievement in hard-to-reach areas.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Radio Instruction to Strengthen Education (RISE) in Zanzibar. Learning gains assessment: more than child's play. - Morris, Emily; Philip, Miriam; Othman, Abrahman Faki; Mitchell, James; Quiones, Esteban J.; Leatxe, Denisse (Education Development Center, Inc. and Ministry of Education and Vocational Training, 2009)
Students at a RISE learning center, who now have access to an early childhood education. RADIO INSTRUCTION TO STRENGTHEN EDUCATION (RISE) IN ZANZIBAR LEARNING GAINS ASSESSMENT:…

Improving teaching quality in Guinea with interactive radio instruction - Burns, Mary (2006)
Guinea's Sous le Fromager project is an excellent example of radio as an effective delivery system for enhancing teachers’ basic content skills and for helping teachers with little or no instructional skills acquire those skills.

Improving Educational Quality through Interactive Radio Instruction - World Bank (2005)

Tuned In To Student Success Assessing the Impact of Interactive Radio Instruction for the Hardest-to-Reach - Ho, J.; Thukral, H.; Laflin, M. (2009)
A review of recent research was conducted to assemble evidence on the impact that Interactive Radio Instruction (IRI) may have on improving student learning outcomes. IRI is an instructional tool designed to deliver a family of active learning packages via radio broadcast using a dual-audience approach. IRI exposes students to regular, curriculum-based learning content while modeling effective learning activities and classroom organization techniques for teachers. As IRI continues to be called upon to improve teaching and learning in low-resource and hard-to-reach areas, a better understanding of the empirical data available is critical to guide the way forward. IRI has been implemented by Education Development Center, Inc. (EDC) in over 50 countries over the past 30 years. This paper is a review of existing student and teacher data collected by EDC’s IRI projects. Effect sizes are used to summarize what is known about the effect of IRI on student learning gains in Grades K-4 for English, Mathematics, Science, Social Studies, and Local Language. In all, student test results from 13 projects, ranging from Nicaragua in 1977 through Indonesia in 2008, are reviewed, as are teacher observation outcomes from Mali and Madagascar.
Keywords: ⛔ No DOI found

Interactive Radio Instruction: An Update from the Field - Bosch, Andrea; Rhodes, Rebecca; Kariuki, Sera (Education Development Center, 2002)
Interactive radio instruction (IRI), a methodology developed to turn a typically one-way technology into a tool for active learning in and outside the classroom, continues to be an attractive educational strategy in developing countries after almost 30 years. The original model for IRI math, created in Nicaragua by a team from Stanford University in the early 1970s, sought to combine the low cost and high reach of the radio medium and a clear understanding of how people learn. Since that time, 20 countries around the world have developed IRI programs for a variety of subjects, audiences, and learning environments, many of which have been sustained for up to 10 years and counting. The methodology has been expanded and adapted to include different levels of math, science, health, English, Spanish and Portuguese, environmental education, early childhood development, and adult basic education for learners of all ages. In each case, the series has been designed specifically by local specialists to be engaging and to meet learning objectives in that country. After three decades, interest in IRI does not seem to be waning. (See the Annex at the end of this chapter for a list of IRI projects and their current status.) This chapter updates earlier information about interactive radio instruction over the past five years, and introduces two cases where IRI has had an impact in Africa in two ways not captured in the past.1 In Guinea, IRI has gone to scale on an unprecedented level in West Africa to reach students and teachers on a national level. The Guinean IRI series is integrated with teacher development initiatives and is used in almost all primary schools across the nation, with 880,000 students. In Zambia, a new IRI series is being developed that reaches out to students who otherwise would be without schools, and have become increasingly vulnerable due to poverty and the HIV/AIDs. This example shows how IRI can be used effectively to overcome obstacles of access in Africa and to increase the chances that students can receive an education. These examples show how IRI retains its core elements, yet continues to evolve to meet new educational and social challenges.

Sustainability and interactive radio instruction: why some projects last - Bosch, Andrea (Adapting Technology for School Improvement A Global Perspective, 2004)
This book presents a compilation of articles based on the premise that the move to advanced technology use in primary and secondary schools offers great hope for improving the access, quality, and efficiency of basic education. The aim of the book is to identify and examine how information technologies can be, and are being, used to strengthen the quality of primary and secondary education. The articles take a global focus, drawing on examples from a wide range of countries. The book analyzes the challenges that teachers and educational planners face as they make this move, and shares how those challenges are being met in some of the countries now engaged in this effort. Several major themes are explored: the role of technology in school improvement, top-down versus bottom-up approaches, interactive radio instruction in schools, computers in the classroom, technology in teacher education, and adopting and implementing technology. The conclusions of the book examine strategies such as the cross-national sharing of curriculum development and instructional materials, and the training and support of teachers and administrators. The need for new partnerships, such as public-private and central-local, to make continued developments in technology sustainable, are also examined. The book divides into 14 chapters: (1) The Role of Technology in School Improvement (David W. Chapman, Amy Garrett, and Lars O. Mahlck); (2) Are New Technologies Better Technologies? For Whom? (Claudio de Moura Castro); (3) International Uses of Education Technology Threats and Opportunities (Stephen P. Heyneman and Katherine Taylor Haynes); (4) Using Instructional Technology as a Bridge to the Future: Palau's Story (Gregory C. Sales and Masa-Aki N. Emesiochl); (5) The Introduction of Computers in Secondary Schools in Jamaica: A Case of Bottom-Up Reform (Errol Miller); (6) Distance Education in Ethiopia (Teshome Nekatibeb and Thomas Tilson); (7) Sustainability and Interactive Radio Instruction: Why Some Projects Last (Andrea Bosch); (8) Is Constructivism Universal? In Search of Meaningful Technology in Morocco and Namibia (Jeffrey Coupe, Jeffrey Goveia, Houcine El Haichour, and Alfred Ilukena); (9) Technology and Educational Change at the Local Level: The Case of the Campana Schools Network in Argentina (Cecilia Braslavsky and Laura Fumagalli); (10) The Pedagogical Uses of Web-Based Chat: The Brazilian Experience (Vera Atsuko Suguri, Maria de Lourdes Matos, Noara M. de Resende e Castro, Rosal va Ieda V. Guimaraes de Castro, Lurdes Marilene da Silva Jung, and Eric Rusten); (11) Utilizing Technology in a Rural Teacher Certification Programme in Iceland (Ingolfur Asgeir Johannesson and Anna Thora Baldursdottir); (12) Integrating Technology into Education: The Czech Approach (Bozena Mannova); (13) The School Online Initiative in German Schools: Empirical Results and Recommendations to Improve School Development (Renate Schulz-Zander); and (14) Effective Use of Technology to Improve Education: Lessons for Planners (Lars O. Mahlck and David W. Chapman). This book is intended for educational policymakers, administrators, planners, and curriculum development specialists concerned with how technology can be used to extend access and raise the quality of education in their countries. It is also intended for international organizations, development assistance agencies and NGOs that are often most responsible for advocating the use of technology as a solution to education problems in low and middle-income countries. (Individual chapters contain references.).
Keywords: Commitment; Cost; content

A Study on The Implementation of English Interactive Radio Instruction (IRI) in Selected Government Primary Schools in Addis Ababa - Alaro, Meseret (Addis Ababa University, 2007)
As its central objective, this study attempts to assess the implementation of English Interactive Radio Instruction (IRI) in selected government primary schools in Addis Ababa. In line with that, the researcher has framed specific questions that address issues related to classroom management, training given to the teachers, links among different stakeholders and the suitability and clarity of the program. Students and teachers of Grade Three from Biherawi Betemengist, Edget Besira , Karalo , Lafto and Salayish Primary Schools are participants of this study .To undertake the study descriptive research design is used . Accordingly, data that is pertinent to the study is collected using different tools such as questionnaire, observation, focus group discussion, interview and document analysis. The findings of the study reveal that the implementation of the program seems to face grave challenges. These mainly emanate from loose link among stakeholders, failure of supplying basic facilities needed to promote the fruitfulness of the program and failure to arrange suitable conditions for the broadcast. Moreover, based on the opinion of the participants, results of the study highlight that in some cases contents of the program is not suitable compared to the students language proficiency .It is also noticed from the findings of the study that classroom practice is not effectively carried out as per the very goal of the program. Despite that, both students and teachers forward positive comments about the utilization of the program for the teaching of English. Based on the findings recommendations for better service and suggestions for further studies are given.

Tuned in to Student Success, Assessing the impact of Interactive Radio Instruction for the hardest-to-reach - Ho, Jennifer; Thukral, Hetal (Journal of Education for International Development, 2009)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Tuned in to Student Success: Assessing the Impact of IRI - Education Development Center, Inc. (2009)
This study reviews student assessment data collected from 15 EDC projects to determine the impact of interactive radio instruction (IRI) on student achievement in hard-to-reach areas.

Developing an HIV/AIDS Education Curriculum for Takalani Sesame, South Africa's Sesame Street - Segal, Lauren; Cole, Charlotte Frances; Fuld, Janice (Early Education and Development, 2002)
The HIV/AIDS pandemic in South Africa has prompted a need for extensive efforts to educate citizens of all ages about the disease and ways of coping with its impact. This paper describes the process of developing an HIV/AIDS education curriculum for Takalani Sesame, an educational media project for young South African children. The process began with formative research with adults and children, and extensive discussions with HIV/AIDS health specialists. Guided by the research and advice from specialists, a team of educators developed a comprehensive curriculum that the Takalani Sesame production team will use to create HIV/AIDS education messages for television, radio and outreach materials for children ages 3-7 and the adults who care for them.

Emerging Technologies: An Overview of Practices in Distance Education - Hussain, Irshad (Journal on School Educational Technology, 2007)
In contemporary society, information technologies and communication technologies (ICTs) are playing crucial role in dissemination of knowledge and information the world over. Universities/ higher education institutions, particularly distance education universities in developed countries are making best use of these technologies for effective and interactive teaching learning process. Developing countries are also trying to adopt the model of developed countries according to their resources and circumstances. Distance education universities in developed countries like United States of America and United Kingdom are using advanced (emerging) technologies such as computers, Internet (World Wide Web) satellite communication, teleconferencing (videoconferencing and audio conferencing) and virtual reality in education and training. In developing countries like India, Pakistan and Thailand, distance education universities are using Radio, Television and Internet for teaching learning purpose and students support services. They are using computers mostly for office work. They are trying to adopt advanced technologies like developed countries but they have some limitations of resources (human & material resources). In future it is hoped that developing countries will also be using emerging technologies for teaching learning purpose.
Keywords: Case Studies; Computer Mediated Communication; Distance Education; Educational Development; Educational Practices; Educational Technology; Educational Television; Foreign Countries; Influence of Technology; Information Networks; Online Systems; Open Universities; Technological Advancement; Technology Integration; Technology Uses in Education; Telecommunications; Virtual Universities

The gender digital divide in rural Pakistan: How wide is it and how to bridge it? - Siegmann, K. A. (Fostering Sustainable Development in South Asia: Responding to Challenges, 2009)
textabstractWhile Pakistan’s National Information Technology (IT) Policy aims at harnessing the potential of information and communication technologies (ICTs) for development, especially in the underserved rural areas, it ignores the role of existing gender inequalities on the possible benefits of ICTs. We have investigated aspects of the ‘gender digital divide’ in rural areas of Pakistan in order to enable an evidence-based gender-sensitive revision of the policy as well as ICT-related interventions from which both females and males gain. The study took place in four of the most marginalized rural districts of the country where this divide is likely to be most pronounced. We found mobile phones to be the ICT that is most commonly available in rural Pakistan. Radios and TV sets are the second most widespread technologies in marginalised rural areas. However, mobile sets at hand are largely owned by women’s husbands, fathers and brothers, whose permission to make calls is required by a large share of all female respondents. I, therefore, argue that availability and gendered use of ICTs are two different things altogether. Social norms related to women and girls’ access to education as well as regulating their mobility prevent them from using ICTs. These norms have to be taken into account in policies and interventions to ensure women and girls’ access to and beneficial use of ICTs.